Biventricular thrombosis and survival after two different mechanical supports before heart transplantation. Issue 7 (17th April 2020) - Ricarte Bratti, Juan Pablo; Chronopoulos, Alexandra; Sia, Ying Tung; Carrier, Francois Martin; Denault, André Y.
Abstract: Patient survival from biventricular thrombosis is possible using mechanical support followed by cardiac transplantation. Abstract : Patient survival from biventricular thrombosis is possible using mechanical support followed by cardiac transplantation.